2000
DOI: 10.1002/1097-0215(20000901)87:5<716::aid-ijc14>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

In vivo therapy of malignant melanoma by means of antagonists of αv integrins

Abstract: Integrin alphavbeta3 (vitronectin receptor) has been implicated in human malignant melanoma progression and angiogenesis as a receptor that provides survival signals. However, little is known about the therapeutic potential of antagonists of alphavbeta3. In this report, we characterize the activities of 2 antagonists of alphavbeta3 integrins: a human specific monoclonal antibody (MAb), 17E6, and a cyclic RGD peptide that blocked cell adhesion and induced detachment of previously substrate-attached cells in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
66
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 0 publications
7
66
0
1
Order By: Relevance
“…22 In concordance with our data, Mitjans et al 23 recently reported that the pan-␣v monoclonal antibody 17E6 and an RGD peptide detached M21 melanoma cells from vitronectin and that only ␣v␤3-expressing melanoma growth was inhibited by this antibody. Similarly, Chatterjee et al 24 reported that a cyclic RGD peptide, similar to ours, induced cell death in the ␣v␤3-expressing brain tumor cells U87MG and U373MG when cells were grown in tissue culture as monolayers or as spheroids, but it had no effect on U251 cells, which lack expression of ␣v␤3.…”
supporting
confidence: 91%
“…22 In concordance with our data, Mitjans et al 23 recently reported that the pan-␣v monoclonal antibody 17E6 and an RGD peptide detached M21 melanoma cells from vitronectin and that only ␣v␤3-expressing melanoma growth was inhibited by this antibody. Similarly, Chatterjee et al 24 reported that a cyclic RGD peptide, similar to ours, induced cell death in the ␣v␤3-expressing brain tumor cells U87MG and U373MG when cells were grown in tissue culture as monolayers or as spheroids, but it had no effect on U251 cells, which lack expression of ␣v␤3.…”
supporting
confidence: 91%
“…17E6 can strongly perturb cell attachment mediated by α v integrins and inhibit cell attachment to α v ligands such as vitronectin and fibronectin. Using a panel of six human melanomas and five carcinomas, 17E6 efficiently blocked the in vivo tumor growth of integrin α v β 3 -positive xenografts but did not affect the α v β 3 -negative xenografts [Mitjans et al, 2000;Mitjans et al, 1995]. Given that mAb 17E6 also does not recognize murine α v β 3 , the anti-tumor effect is likely due to the direct antitumor activity, and not to the anti-host vasculature activity in the mouse model.…”
Section: Integrin α V β 3 Inhibitorsmentioning
confidence: 99%
“…Cilengitide has demonstrated preclinical single-agent anti-tumor activity against melanoma [96] and orthotopic brain tumor xenografts [36,71], which may be due to apoptosis induced by tumor cell detachment [71]. Recent preclinical work has focused on the clinical observation that MGMT methylated tumors tend to respond positively to cilengitide combined with XRT/TMZ compared to MGMT unmethylated tumors [43].…”
Section: Pharmacodynamics and Preclinical Studiesmentioning
confidence: 99%